The influence of sexual dimorphism on the manifestation of coordination abilities of volleyball players aged 15-17 - Boichuk, R.; Iermakov, S.; Vypasniak, I.; Nosko, M.; Nosko, Y.; Harkusha, S.; Vaskan, I.; Grashchenkova, Z.; Ivanyshyn, I. (Pedagogy of Physical Culture and Sports, 2024)
Background and Study Aim. Sexual dimorphism plays a crucial role in the design of training programs for athletes. Therefore, understanding the influence of sexual dimorphism on various abilities is essential for optimizing training regimens. The aim of this study is to determine the influence of sexual dimorphism on the manifestation of coordination abilities in young volleyball players aged 15-17.